1977
DOI: 10.1080/10408347308000741
|View full text |Cite
|
Sign up to set email alerts
|

The education and career patterns of professional Mechanical Engineers in design and management

Abstract: Engineering design and the profesional engineer In historical terms engineering design has been closely associated with engineering management: Brunel was a designer who personally controlled the construction of his designs. Perhaps Sir Henry Royce was the archetype of designer/manager: Director and Chairman of the board, he was responsible for every single aspect of the design of the early Rolls Royce engines. There exists today very few large single product firms in which such individuals could flourish. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…EER in the UK stretches back to the end of WWII (Bosworth, 1963;1966;Heywood, 1969;1970;Heywood & Monk, 1977;Ministry of Education, 1945;1956). Despite this long history, more recent studies have found that UK academics dedicate little time to EER; the field is marked by low levels of publication, and a lack of resources and financial support (Shawcross & Ridgman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…EER in the UK stretches back to the end of WWII (Bosworth, 1963;1966;Heywood, 1969;1970;Heywood & Monk, 1977;Ministry of Education, 1945;1956). Despite this long history, more recent studies have found that UK academics dedicate little time to EER; the field is marked by low levels of publication, and a lack of resources and financial support (Shawcross & Ridgman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The design of courses to prepare engineers for the reality of engineering is difficult and requires radically new approaches. Problem based learning pioneered by Woods in engineering [9][10] and project based learning schemes 11 may go some way toward meeting this need.…”
Section: They Defined Transdisciplinarity "As the Integrated Use Of [mentioning
confidence: 99%